Reflexos da judicialização da saúde no acesso igualitário a políticas públicas: a questão dos leitos de UTI no estado do Ceará - Leite, Vanessa Gomes (2016)
Through this research, it was done a critical analysis of judicialization health reflections on equal access to public policies, focusing the analysis of the issue of ICU beds in the state of Ceará. Adopted a bibliographical, exploratory and inductive of their results research, aimed at improving the thoughts by collecting information on the subject in focus. First evaluated the assumptions and characteristics of the right to health as a fundamental right and the duty of the State as guarantor of benefits to health in the context of the constitutional principles that govern this state commitment. In order to define better its contents, were discussed the elements that fill and limited it, as social determinants, legal nature, and the scarcity of financial resources. Moreover, analyzed the definition and procedures inherent to the achievement of public policy, discussing the aspects related to the planning guidelines of public health policies. After, Judiciary positions in the decision relating to public policy were evaluated. Anyway, were discussed the consequences of injunctions concessions requests to ICU beds in the state of Ceará in front of an existing queue. In front of an excessive judicialization combined with the predominance of a single litigation that encourages microjustice, were analyzed the benefits that collective demands can produce to solve this problem that affects many years the Ceará population. In this way, it is concluded that the collective action reveals itself an authentic dialogic mechanism, in which the judge comes more as an arbitrator, as an inductor, to drive the process towards a negotiated settlement. It is believed that the Judiciary can contribute when expands the channels to discuss the best way to allocate scarce resources, plan management services and treatments, including intensive care beds, and increase the exchange of information between the organs themselves and between them and the patients.